Лисичка Тыковка, или Лунный камень: [повесть] / Дейзи Медоус - Медоус Дейзи (Лес Дружбы, 2019)
Экземпляры: ф.12 (20190314) / Инвентарный номер: 56787 / Цена: 99.00 / Авт.знак: М 42 / ГРНТИ: 17.82.93 / ББК: 84(4Вел)-44